FRUGAL INNOVATION IN TEACHING PRACTICE FOR YOUTH AND ADULT EDUCATION: INCLUSION OF AUTISTIC ADULTS IN CONTEXTS OF SCARCITY (Editora Impacto Científico, 2026)
This article analyzes the emergence of Frugal Innovation in the teaching practice of Youth and Adult Education (EJA) as a pedagogical strategy for the inclusion of adults with Autism Spectrum Disorder (ASD) in contexts marked by resource scarcity. This is a qualitative study of a theoretical-analytical nature, based on a critical narrative review of national and international literature on EJA, inclusive education, Frugal Innovation, and simple educational technologies. The results show that, in the face of structural precariousness, the fragility of public policies, and the insufficiency of specific teacher training, EJA teachers develop creative pedagogical practices based on the use of accessible and low-cost technologies, configuring legitimate processes of Frugal Innovation. Such practices broaden the participation, autonomy, and engagement of autistic adults, while simultaneously challenging normative curricula and denouncing the naturalization of educational precariousness. It is concluded that Frugal Innovation, far from replacing public policies, constitutes a form of curricular resistance ethically committed to social justice, neurodiversity, and the right to lifelong education.DOI: https://doi.org/10.56238/edimpacto2025.090-090